Mapping the global burden of early-onset Parkinson’s disease: socioeconomic and regional inequalities from the Global Burden of Disease Study 2021 - Li, Xinyu; Zhou, Jingpei; Peng, Wanqing; Zhao, Renhui; Sun, Quan; Liu, Zhijuan; Liu, Yanning; Li, Ziyuan; Huang, Ziting; Zhang, Yihui; Zhang, Shuqiao; Hong, Xubo; et al. (Frontiers in Public Health, 2025)
BackgroundsEarly-onset Parkinson’s disease (EOPD) presents a significant financial burden on healthcare systems and medical expenses. However, there has been a lack of comprehensive quantitative assessments to fully understand the extent of this burden. The Global Burden of Diseases (GBD) initiative aims to provide a standardized and thorough evaluation of these factors on a global, regional, and national scale. This study aimed to calculate the global burden of EOPD and characterize regional disparities, SDI-based inequalities, and gender differences in disease burden, with a focus on trends from 1990 to 2021.MethodsWe utilized data from the GBD Study 2021 to analyze the burden of EOPD by examining factors such as incidence, prevalence, disability-adjusted life years (DALYs), and mortality rates. We focused on trends in EOPD incidence, prevalence, DALYs, and deaths from 1990 to 2021. Additionally, socio-demographic index (SDI)-related determinants that influence EOPD DALYs and characterized the disparities in EOPD burden associated with different SDI levels over the same period.ResultsIn EOPD, a significant increase in age-standardized rates for incidence, prevalence, and DALYs while the death rate declined. Males exhibited a higher burden than females across all metrics. Geographic disparities showed that East Asia had the highest rates of incidence and DALYs, while Andean Latin America recorded the highest prevalence. Countries with higher SDI levels, particularly China, Bolivia, and Peru, bore the greatest burden. Socioeconomic patterns suggested high-middle SDI regions experienced the highest rates of incidence and prevalence, whereas middle-SDI regions showed the highest rates of disability and mortality. Decomposition analysis revealed population growth was the primary driver of increased DALYs in middle-SDI regions. Additionally, inequality analysis indicated that countries with higher SDI levels faced a disproportionately lower burden of disease.ConclusionThis study confirms a global increase in the burden of EOPD, and indicate rising incidence and prevalence rates, an increase in DALYs, and a decline in mortality rates. A notable predominance of male cases, along with significant geographic and socioeconomic disparities. Regions with a middle SDI experience the most significant burden of disability and mortality, primarily driven by population growth. This underscores the urgent need for targeted interventions to address these inequities.